The Scientific Revolution of Thomas Kuhn and Their Relevances for Humanization of Islamic Law - Muhamad Ali Mustofa Kamal (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2016)
This paper tries to explore the views of Thomas Kuhn that science is moving through the stages that will culminate in normal conditions and then "rot" because it has been replaced by science or new paradigm. So next. The new paradigm threatens the old paradigm that had previously become the new paradigm. With this thinking concept, Thomas Kuhn is not just a major contribution in the history and philosophy of science, but more than that, he has initiated the theories that have broad implications in the social sciences, arts, politics, education and even religious sciences , provide an important contribution in order to project humanization Islamic sciences. in showing Islamic humanist deconstruction re the primary sources of Islam, namely the Qur'an and Tafseer already should keep abreast of the needs of Muslim humanist paradigm so that the functional interpretation theories and theories of literacy is very possible to grow, to challenge the needs of the times.